1999
DOI: 10.2135/cropsci1999.0011183x003900010035x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Similarities among Winter Wheat Cultivars Determined on the Basis of RFLPs, AFLPs, and SSRs and Their Use for Predicting Progeny Variance

Abstract: The efficiency of breeding programs could be increased by predicting the prospects of crosses for line development before producing and testing lines derived from them. In this study, we (i) assessed the level of genetic diversity among German and Austrian winter wheat (Triticum aestivum L.) cultivars using 117 restriction fragment length polymorphism (RFLP) probes, 16 amplified fragment length polymorphism (AFLP) primer combinations, and 21 simple sequence repeat (SSR) primer pairs, (ii) investigated the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
138
4
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(178 citation statements)
references
References 0 publications
28
138
4
8
Order By: Relevance
“…Marker attributes like PIC, MI and Rp have been used in several studies to assess the discriminatory power of AFLP markers for genetic diversity analysis (Powell et al 1996;Bohn et al 1999;Muminovic et al 2004;Leela Tatikonda et al 2009). In this first comprehensive study, we have analyzed these attributes for AFLP studies in Mucuna species.…”
Section: Discriminating Power Of Aflp Based On Marker Attributesmentioning
confidence: 99%
“…Marker attributes like PIC, MI and Rp have been used in several studies to assess the discriminatory power of AFLP markers for genetic diversity analysis (Powell et al 1996;Bohn et al 1999;Muminovic et al 2004;Leela Tatikonda et al 2009). In this first comprehensive study, we have analyzed these attributes for AFLP studies in Mucuna species.…”
Section: Discriminating Power Of Aflp Based On Marker Attributesmentioning
confidence: 99%
“…Studies in wheat (Triticum aestivum), oat (Avena sativa) and soybean (Glycine max) suggest that pedigree divergence between parents, estimated on the basis of the coefficient of parentage (Kempthorne, 1969), could be used to predict genetic variance in F 2 or later segregating generations (Bhatt, 1970(Bhatt, , 1973Cowen and Frey, 1987;Manjarrez-Sandoval et al, 1997). However, other studies in the same species (Moser and Lee, 1994;Helms et al, 1997;Kisha et al, 1997;Burkhamer et al, 1998;Bohn et al, 1999) indicated that the relationship between parental pedigree distance and progeny genetic variance was neither consistent nor strong enough to permit reliable prediction of genetic variance. One possible explanation for the limited relationship between pedigree divergence and progeny variance observed in these studies is that coefficients of parentage may be inaccurate because the parents of some specific crosses might differ for many genes affecting a trait.…”
Section: Introductionmentioning
confidence: 99%
“…Although GD estimates based on molecular marker estimates have been effective at grouping related germplasm (Melchinger et al, 1998), the relationship between GD in parents and genotypic variance components (GVCs) in their progenies has been reported as weak or non-significant across many studies (Helms et al, 1997;ManjarrezSandoval et al, 1997;Burkhamer et al, 1998;Melchinger et al, 1998;Bohn et al, 1999;Gumber et al, 1999;Brachi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of different DNA markers for diversity studies in maize (Hahn et al, 1995;Smith et al, 1997;Ajmone Marsan et al, 1998;Pejic et al, 1998), barley (Russell et al, 1997), wheat (Bohn et al, 1999), cruciferous species (dos Santos et al, 1994;Thormann et al, 1994), potato (Mc Gregor et al, 2000), sorghum (Yang et al, 1996) and rice (Davierwala et al, 2000) have tried to evaluate the relative efficiencies of the different techniques available. However, in the case of maize, tropical and temperate populations differ from each other because tropical populations usually originate from composites with higher genetic variability and, most of the time, it is difficult to allocate tropical composites to well-defined heterotic groups by phenotypic evaluation.…”
Section: Introductionmentioning
confidence: 99%